A Preliminary Study Exploring the Impact of Learner Resilience under Enforced Online Delivery during the COVID-19 Pandemic - Tom Crick (Proceedings of the 26th ACM Conference on Innovation and Technology in Computer Science Education V. 2, 2021)
This poster presents the preliminary findings from a research project exploring the impact of the COVID-19 pandemic on learner resilience from the shift to online delivery of learning and teaching amidst national social "lockdown" measures. This exploration of resilience was undertaken as part of the delivery of the first-year undergraduate computer science degree programme in a UK university. Resilience was measured by the Nicholson McBride Resilience Questionnaire (NMRQ) and three open-ended questions exploring what has supported their study most during the COVID-19 pandemic, what had been the greatest challenge, and how that challenge was resolved.The preliminary results of this survey (N=103) illustrate how learner responses differed to the delivery depending upon their measured resilience level. Additionally, the results provide valuable insight into learners’ perceptions of the challenges of online learning, teaching and assessment. Given the continued impact on educational settings from COVID-19, online/blended learning is likely to remain a significant feature of future delivery; hence the insights offered from this UK institutional study can inform future sector practice.